Pengaruh Penggunaan Teknologi ChatGPT Terhadap Kualitas Tugas Siswa Kelas X Di SMA Gorontalo - Novian, Dian; A., Hermila; Sudirman, Randi (VOCATECH: Vocational Education and Technology Journal, 2024)
AbstractThe popularity of AI technology in learning has increased significantly. One example is ChatGPT, an AI model developed by OpenAI using the ‘Generative Pre-trained Transformer’ (GPT) architecture to automatically generate conversational text. This study aims to evaluate the contribution of artificial intelligence (AI) technology, specifically ChatGPT, in improving the quality of student assignments. Using a causality method with a quantitative approach, this study involved 81 grade X students at SMA Negeri 1 Gorontalo. The research was conducted through four main stages, namely preliminary studies, data collection, data analysis, and report writing. Based on the validity test with a sample of N=35 at the 5% significance level, the variabel X statement instrument was declared valid. Meanwhile, the reliability test showed a Cronbach's Alpha value of 0.759, which means that the indicators of student assignment quality were declared reliable. The results of the simple regression analysis revealed that the tcount of 1.770 was greater than the ttable of 1.994 at the 5% significance level, so Ha was accepted and Ho was rejected. Thus, there is a significant effect of using AI ChatGPT technology on improving the quality of student assignments, indicating that this AI contributes effectively to the learning process.Keywords:AI Technology; ChatGPT; Student assignments AbstrakPopularitas teknologi AI dalam pembelajaran menunjukkan peningkatan signifikan. Salah satu contohnya adalah ChatGPT, model AI yang dikembangkan oleh OpenAI dengan menggunakan arsitektur "GenerativePre-trainedTransformer" (GPT) untuk menghasilkan teks percakapan secara otomatis. Penelitian ini bertujuan untuk mengevaluasi kontribusi teknologi kecerdasan buatan (AI), khususnya ChatGPT, dalam meningkatkan kualitas tugas siswa. Menggunakan metode kausalitas dengan pendekatan kuantitatif, studi ini melibatkan 81 siswa kelas X di SMA Negeri 1 Gorontalo. Penelitian dilakukan melalui empat tahapan utama, yakni studi pendahuluan, pengambilan data, analisis data, dan penulisan laporan. Berdasarkan uji validitas dengan sampel N=35 pada tingkat signifikansi 5%, instrumen pernyataan variabel X dinyatakan valid. Sementara itu, uji reliabilitas menunjukkan nilai Cronbach's Alpha sebesar 0,759, yang berarti indikator kualitas tugas siswa dinyatakan reliabel. Hasil analisis regresi sederhana mengungkapkan bahwa thitung sebesar 1,770 lebih besar dari ttabel sebesar 1,994 pada taraf signifikansi 5%, sehingga Ha diterima dan Ho ditolak. Dengan demikian, ada pengaruh signifikan dari penggunaan teknologi AI ChatGPT terhadap peningkatan kualitas tugas siswa, menunjukkan bahwa AI ini berkontribusi efektif dalam proses pembelajaran.Kata Kunci:      Teknologi Ai; ChatGPT; Tugas siswa